Self-Independent Computer Operation by Children in Early Childhood Education - Lutfitra Rahmilla Rizqika; Ade Dwi Utami (SEAMEO CECCEP, 2024)
This research investigates how young children in early childhood education settings using computers independently. It studies the independent way in which children engage with and gain knowledge from computer technology, without the need for continuous adult monitoring. By conducting qualitative observation and analysis, the study investigates the developmental advantages, obstacles, and consequences of individuals interacting independently with computers. This research focuses on how children interact with technology and how it affects their learning. Observation of children, interviews with teachers, and documentation of children's learning were used to collect data. The findings of this study reveal that kids use computers on their own and play educational games to enhance their learning. Research indicates that being exposed to independent computer use at a young age promotes digital literacy, problem-solving skills, and self-directed learning in children. The research results suggest that incorporating ICT into early childhood education shows great potential for improving children's learning experiences. The study underscores the importance of balancing technological access with pedagogical support to optimize educational outcomes in early childhood contexts.